2023
DOI: 10.1021/acs.orglett.2c04145
|View full text |Cite
|
Sign up to set email alerts
|

Site-Selective Functionalization of Unactivated Allylic C–H Bonds via Direct Deprotonation with KTMP: Application to the Formal Total Synthesis of (+)-Artemisinin from Amorphadiene

Abstract: The site-selective functionalization of unactivated allylic C–H bonds via direct deprotonation using KTMP is described. The conversion of amorphadiene to artemisinic alcohol via a simple, highly regioselective deprotonation over 4 other possible allylic sites is shown with further extrapolation to the first large-scale telescoped chemical synthesis of artemisinic acid from amorphadiene. Finally, application of the method for the successful site-selective functionalization of unactivated allylic C–H bonds in ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In order to augment the plant-based supply of artemisinin ( 32 ) for anti-malarial drug production, a biotransformation driven process for artemisinin was developed at Sanofi, starting from its biosynthetic terpene precursor amorphadiene ( 72 ) (Scheme 16). 57 The critical step involved a highly regioselective allylic oxidation of 72 which was carried out using an enzymatic C–H hydroxylation reaction, a far superior process over chemical methods, 58 to produce the key intermediate artemisinic alcohol ( 73 ).…”
Section: Approaches To Api Processingmentioning
confidence: 99%
“…In order to augment the plant-based supply of artemisinin ( 32 ) for anti-malarial drug production, a biotransformation driven process for artemisinin was developed at Sanofi, starting from its biosynthetic terpene precursor amorphadiene ( 72 ) (Scheme 16). 57 The critical step involved a highly regioselective allylic oxidation of 72 which was carried out using an enzymatic C–H hydroxylation reaction, a far superior process over chemical methods, 58 to produce the key intermediate artemisinic alcohol ( 73 ).…”
Section: Approaches To Api Processingmentioning
confidence: 99%
“…Subsequently, Walsh’s group, Guan’s group, Zhao’s group, and Wu and co-workers developed the functionalization of C­(sp 3 )–H bonds via direct deprotonation using MN­(SiMe 3 ) 2 bases (M = Li, Na, K, and Cs). In 2023, Frantz et al described an effective site-selective allylic C­(sp 3 )–H functionalization protocol with KTMP for the total synthesis of (+)-artemisinin from amorphadiene. In continuation with our previous work on the synthesis of N -heterocyclic compounds, we herein report the LiN­(SiMe 3 ) 2 /KO t Bu-promoted formal [4 + 2] cycloaddition reaction for the one-pot synthesis of isoquinolones via C­(sp 3 )–H bond activation (Scheme d).…”
Section: Introductionmentioning
confidence: 99%
“…Frantz and co-workers have recently demonstrated that a stoichiometric metalation/borylation/oxidation sequence on this substrate selectively affords 10-hydroxyperillyl alcohol 36 by activation of the exocyclic isoprene unit. 24 In sharp contrast, 35 mostly reacted through the allyl alcohol residue with an excess of diazene 1a and tBuOK (30 mol %) to afford the α-hydroxysilane 35a in 45% yield after careful hydrolysis of the O−SiEt 3 linkage. In this case, the endocyclic C�C double bond of 35 did not migrate, presumably because the most favorable pathway involves a retro-[1,2]-Brook rearrangement.…”
mentioning
confidence: 99%
“…To further illustrate the synthetic potential of our methodology, we set out to investigate the catalytic silylation of (−)-perillyl alcohol 35 , a naturally occurring terpene that contains up to five potentially reactive allylic positions (Scheme B). Frantz and co-workers have recently demonstrated that a stoichiometric metalation/borylation/oxidation sequence on this substrate selectively affords 10-hydroxyperillyl alcohol 36 by activation of the exocyclic isoprene unit . In sharp contrast, 35 mostly reacted through the allyl alcohol residue with an excess of diazene 1a and t BuOK (30 mol %) to afford the α-hydroxysilane 35a in 45% yield after careful hydrolysis of the O–SiEt 3 linkage.…”
mentioning
confidence: 99%